Grit on Students in Indonesia - Wahidah, Fatin Rohmah Nur; Herdian, Herdian (Technium Social Sciences Journal, 2021)
Grit becomes an aspect that is no less important for students. In Indonesia, the study of grit began to be widely conducted in the field of education. Studies on grit still need to be developed to enrich the literature and discussion, especially the great benefits for students. This research aims to describe about grit students in Indonesia and to enrich the findings and literature about it. This research used quantitative approach. Participants in this study were Indonesian students, aged 16-23 years (418 high school students and 408 college students). The instrument used the Grit Scale for Children and Adult (GSCA) from Sturman and Zappala-Piemme (2017) consisting of 12 items (a = 0.744). Data analysis uses SPSS 26 to help to perform a descriptive analysis of demographics and t-tests. The results of this study showed the level of a grit of students in Indonesia is in the moderate category. This study also showed no significant grit differences neither based on gender nor by grade level of students.